Studi Deskriptif Pembelajaran Ansambel Di SMP Negeri 29 Padang - Sinta Krisma Setia; Erfan Erfan (SENDRATASIK UNP, 2020)
This research is a qualitative descriptive study. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instrument and camera. The data were collected through interviews, literature study, and documentation. The data analysis was conducted by identifying the data, classifying the data, describing the data, and making conclusions. The results show that the learning process for the musical ensemble at SMP Negeri 29 Padang consists of group division, coinciding, selection of musical instruments, and learning of each music / instrument. The music ensemble learning activities are divided into three stages: preparation, practice / process, and evaluation. In the preparation stage, the teacher prepares the teaching document and  subject matter while the students prepare musical instruments. In the practice / process stage, the teacher gives apperception in reminding about the meaning of musical ensembles and types of musical instruments, introducing songs to be played, and providing musical scores as well as techniques for playing recorder and pianica. In the evaluation stage, the teacher assesses, reviews, and sees the success and development of students towards learning.